Study guides

☆☆

Q: The answer to 2x plus 3 equals x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

2x + 2 = 4x -1 2x = 3 x = 1.5

6x + 3 = 2x + 5 4x = 2 x=1/2

2x+8 = 6 2x = 6-8 2x = -2 x = -1

21

2x - 4x + 3 = 0 -2x + 3 = 0 2x = 3 x = 3/2 = 1.5

Related questions

(-1, 3)

2x + 3y = 1 y = 1/3 - 2x/3

(1, 1)

x = 1 ------------- 3 = 2x + 1 -1 -1 2=2x /2 /2 1=x

1

Both equations are equal and so: 3x+1 = 2x+3 3x-2x = 3-1 x = 2 and by substituting y = 7

(2, 1)

2x +1 = 5x-2 2x +3= 5x 3 = 3x x=1

2x + 2 = 4x -1 2x = 3 x = 1.5

(3, 1)

(4, -1)

(-1, 0)

People also asked